2018
DOI: 10.1364/oe.26.003814
|View full text |Cite
|
Sign up to set email alerts
|

Silver-based surface plasmon waveguide for terahertz quantum cascade lasers

Abstract: Terahertz-frequency quantum cascade lasers (THz QCLs) based on ridge waveguides incorporating silver waveguide layers have been investigated theoretically and experimentally, and compared with traditional gold-based devices. The threshold gain associated with silver-, gold- and copper-based devices, and the effects of titanium adhesion layers and top contact layers, in both surface-plasmon and double-metal waveguide geometries, have been analysed. Our simulations show that silver-based waveguides yield lower l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 33 publications
1
16
0
1
Order By: Relevance
“…Recently, our group increased the operating temperature of terahertz QCLs using a design optimized using the IAPT described above and varying the four layer widths to maximize the gain at 300 K. The details of this optimization are given in Supplemental Material [37]. The optimized design had a simulated gain of 25 cm −1 , which predicts a much-higher operating temperature than observed experimentally [7], considering total optical losses of about 20 cm −1 at 300 K for Cu-Cu double-metal waveguides [39]. However, these simulations did not consider the effect of electron-electron (e-e) correlations, which act to redistribute the carriers (thermalization) and greatly reduce the peak gain due to level broadening [40].…”
Section: A Optimization Of the Two-well Terahertz Qclmentioning
confidence: 99%
“…Recently, our group increased the operating temperature of terahertz QCLs using a design optimized using the IAPT described above and varying the four layer widths to maximize the gain at 300 K. The details of this optimization are given in Supplemental Material [37]. The optimized design had a simulated gain of 25 cm −1 , which predicts a much-higher operating temperature than observed experimentally [7], considering total optical losses of about 20 cm −1 at 300 K for Cu-Cu double-metal waveguides [39]. However, these simulations did not consider the effect of electron-electron (e-e) correlations, which act to redistribute the carriers (thermalization) and greatly reduce the peak gain due to level broadening [40].…”
Section: A Optimization Of the Two-well Terahertz Qclmentioning
confidence: 99%
“…For GaAs/AlGaAs THz QCLs, most single and double metal plasmon waveguides use Au as the metal waveguide. More recently both Cu [37] and Ag [38] have been used for double metal waveguides due to their higher electrical and thermal conductivity compared to Au. A comparison of Ag, Au and Cu on GaAs/AlGaAs THz QCLs has demonstrated that Ag provides the lowest waveguide losses and lowest lasing thresholds [38].…”
Section: Materials Choice and Thz Optical Datamentioning
confidence: 99%
“…More recently both Cu [37] and Ag [38] have been used for double metal waveguides due to their higher electrical and thermal conductivity compared to Au. A comparison of Ag, Au and Cu on GaAs/AlGaAs THz QCLs has demonstrated that Ag provides the lowest waveguide losses and lowest lasing thresholds [38]. Au is a fast diffuser and a deep level impurity in Si, Ge and SiO 2 [39][40][41] and therefore it is incompatible with all silicon foundries that might microfabricate Ge/Si 1−x Ge x QCL devices.…”
Section: Materials Choice and Thz Optical Datamentioning
confidence: 99%
“…Со стороны " высоких" частот расстояние между рабочими уровнями (около 20 мэВ для частоты 5 ТГц) становится сопоставимо с энергией LO-фонона в GaAs (E LO = 36 мэВ), что приводит к испусканию LO-фононов " горячими" электронами на верхнем рабочем уровне и уменьшению инверсной населенности. Следует отметить, что в области низких частот 1−2 ТГц наблюдается рост потерь, обусловленных поглощением излучения свободными носителями заряда, а в области частот свыше 6 ТГц -резонансным поглощением на TO-фононах [7,8], что также ограничивает частотный диапазон работы ТГц ККЛ.…”
Section: Introductionunclassified